Financing greener and climate-resilient infrastructure in developing countries - challenges and opportunities - Marianne Fay; Atsushi Iimi; Baptiste Perrissin-Fabert (EIB Papers, 2010)
Developing countries are faced with a substantial and persistent infrastructure deficit. Climate change complicates this challenge, affecting the way we design and manage infrastructure (defined here as transport, power, water and sanitation) and increasing costs. But all is not negative: Climate change affects both the economic and financial analysis of infrastructure projects in a way that could help achieve longpursued but elusive goals, such as better maintenance and greener, more efficient design. Further, climate finance could bring additional financing, although that will require increasing the scale of available resources and addressing the fact that climate finance tends to provide ex post financing, ill-suited to a sector characterized by a need for substantial ex ante funding.
Keywords: 330